The Effect of Sugarcane Juice (Saccharum officinarum) Substitution in Citrate–Egg Yolk Diluent on the Quality of Frozen Semen of Landrace Boars: Pengaruh Substitusi Sari Tebu (Saccharum Offcinarum) dalam Pengencer Sitrat-Kuning Telur terhadap Kualitas Semen Beku Babi Landrace - Paskalis Baylon; Wilmintje Marlene Nalley; Alvrado Bire Lawa; Petrus Kune (BPFP Universitas Bengkulu, 2026)
This study aimed to determine the effect of sugarcane juice substitution in a citrate–egg yolk diluent (CE-Y) on the quality of frozen semen of landrace boars. The semen used in this study was collected from four landrace boars aged between 2–2.5 years using the glove gland method. The study employed a Completely Randomized Design with five treatments and four replications, namely T0 = 100% S-KT + 0% sugarcane juice, T1 = 90% S-KT + 10% sugarcane juice, T2 = 80% S-KT + 20% sugarcane juice, T3 = 70% S-KT + 30% sugarcane juice, and T4 = 60% S-KT + 40% sugarcane juice. All treatments were supplemented with 6% glycerol. Semen was evaluated macroscopically and microscopically. After evaluation, a holding time of 2 hours was applied in S-KT diluent with a ratio of 1:1 at a temperature of 24–26°C. The semen was then centrifuged at 3000 rpm for 15 minutes. The pellet was diluted using a base diluent and then distributed into tubes containing the treatment diluent. The semen was packaged in 0.5 mL straws and equilibrated for 2 hours at 3–5°C. After equilibration, the straws were frozen at a distance of 10 cm above the surface of liquid nitrogen for 10 minutes. The straws were then plunged into liquid nitrogen and stored in a liquid nitrogen container. Thawing was carried out by immersing the frozen semen straws in warm water at 37°C for 30 seconds. After dilution and equilibration, sperm quality was evaluated based on motility, viability, and abnormalities. Post-thaw evaluation included motility, viability, abnormalities, and recovery rate. All obtained data were analyzed using SPSS 27.0. The results showed that sugarcane juice substitution had no significant effect (P>0.05) on motility, viability, abnormalities, and RR. It was concluded that the substitution of sugarcane juice with the addition of citrate–egg yolk diluent did not affect the quality of frozen spermatozoa of landrace boars at the stages of post-dilution, post-equilibration, and post-thawing.